Application research on indoor earthquake early warning information design based on virtual simulation experiment - Lu, Qiyun; Han, Peng; He, Zijian; Wang, Zihan; Wang, Yufei (Frontiers in Virtual Reality, 2025)
This study investigates the critical role of public information in conveying protective guidance during earthquakes, a significant and sudden natural disaster threatening human life and property. Utilizing virtual imitation experiments to simulate earthquake scenarios, we established an experimental group and a control group to assess the impact of indoor Earthquake Early Warning (EEW) on individuals’ hedging behavior. Our findings indicate that the experimental group, which received protective guidance, demonstrated higher accuracy in selecting avoidance areas and required less time compared to the control group, suggesting that protective guidance significantly enhances the correctness and efficiency of earthquake evacuation. Additionally, value functions, weight functions, and prospect values were compared, revealing that the experimental group’s average prospect value was substantially higher, underscoring the necessity for incorporating specific earthquake guidelines in the content of earthquake early warnings. These conclusions offer valuable insights for optimizing earthquake warning system design and enhancing indoor environmental emergency self-rescue and information guidance in residential settings.